2005
DOI: 10.1038/ncb1302
|View full text |Cite|
|
Sign up to set email alerts
|

The endoplasmic reticulum gateway to apoptosis by Bcl-XL modulation of the InsP3R

Abstract: Members of the Bcl-2 protein family modulate outer mitochondrial membrane permeability to control apoptosis1 ,2 . However, these proteins also localize to the endoplasmic reticulum (ER), the functional significance of which is controversial 3, 4. Here we provide evidence that anti-apoptotic Bcl-2 proteins regulate the inositol 1,4,5-trisphosphate receptor (InsP 3 R) ER Ca 2+ release channel resulting in increased cellular apoptotic resistance and enhanced mitochondrial bioenergetics. Anti-apoptotic Bcl-X L int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
444
5
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(479 citation statements)
references
References 32 publications
27
444
5
3
Order By: Relevance
“…Recombinant expression (or addition to the patch pipette) of Bax prevented the effect of Bcl-X L , both in terms of its binding to the IP3R and of capacity of modifying the sensitivity to IP3. 79 The results differ from a previous paper by the Distelhorst group that showed that Bcl-2 reduces the opening probability of IP3Rs inserted into lipid bilayers. 53 As to the mechanism, the Foskett-Thompson paper proposes a direct modulatory role on IP3R (through protein-protein interaction between the two proteins) rather than a phosphorylation event, based on the timing after Bcl-X L addition and the experimental conditions employed (nonpermissive for phosphorylation).…”
Section: Direct Molecular Interaction With Er Channelsmentioning
(Expert classified)
See 1 more Smart Citation
“…Recombinant expression (or addition to the patch pipette) of Bax prevented the effect of Bcl-X L , both in terms of its binding to the IP3R and of capacity of modifying the sensitivity to IP3. 79 The results differ from a previous paper by the Distelhorst group that showed that Bcl-2 reduces the opening probability of IP3Rs inserted into lipid bilayers. 53 As to the mechanism, the Foskett-Thompson paper proposes a direct modulatory role on IP3R (through protein-protein interaction between the two proteins) rather than a phosphorylation event, based on the timing after Bcl-X L addition and the experimental conditions employed (nonpermissive for phosphorylation).…”
Section: Direct Molecular Interaction With Er Channelsmentioning
(Expert classified)
“…80 Finally, the Foskett-Thompson paper, by looking at sensitivity to apoptosis of DT40 cells in which all three IP3R isoforms had been deleted, shows that basal activation of the IP3R not only partially depletes the Ca 2 þ store but also provides a 'survival' signal per se (possibly by activating mitochondrial metabolism), given that the KO cells are more sensitive to apoptotic challenges than the wild-type cells. 79 Also in this case, given the robust evidence for the role of mitochondrial Ca 2 þ uptake in facilitating PTP opening and proapoptotic mitochondrial changes, it seems fair to conclude that Bcl-2 globally reprogrammes ER Ca 2 þ release and mitochondrial Ca 2 þ loading, as necessary for optimally activating apoptosis (in terms of metabolic requirements as well as prompt release of caspase cofactors into the cytosol).…”
Section: Direct Molecular Interaction With Er Channelsmentioning
confidence: 91%
“…In a second role, Bcl-XL by its association with VDAC, has been shown to regulate flow of ATP/ADP in and out of mitochondria (Vander Heiden et al, 1999). Additionally, Bcl-XL was shown to bind the inositol 1,3,5-triosephosphate receptor in the endoplasmic reticulum resulting in increased cellular apoptotic resistance and enhanced mitochondrial bioenergetics (White et al, 2005). Consequently, there is now a clear relationship established between the cellular energetics and anti-apoptosis proteins in the mitochondria and other cellular compartments including the endoplasmic reticulum.…”
Section: Intertwining Apoptosis and Metabolismmentioning
confidence: 99%
“…The central metabolic role of the mitochondria was initially considered distinct from its contribution to apoptosis. While the functionality of the apoptotic proteins still holds true, it is now evident that these proteins also play roles in the metabolic processes of the mitochondria (see Majors et al, 2007 for a review; White et al, 2005). Furthermore, apoptosis pathway proteins in other organelles within the cell may modulate both apoptosis and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that members of the BCL-2 family reside not only in the OMM but also in the ER where they have opposing actions in regulating the transfer of ER Ca 2 þ to mitochondria; antiapoptotic members reduce ER Ca 2 þ and pro-apoptotic members promote Ca 2 þ mobilization from the ER to mitochondria during apoptosis, perhaps by regulating of the activity of the ER inositol trisphosphate receptor. [43][44][45] Thus, the action of the PT and BCL-2 family members may be harmonized through the ability of BCL-2 proteins to regulate the levels of ER Ca 2 þ , the key trigger of the mitochondrial PT.…”
Section: An Integrated Modelmentioning
confidence: 99%